Oral Administration of Piperine as Curative and Prophylaxis Reduces Parasitaemia in Plasmodium berghei ANKA-Infected Mice - Shafia Khairani; Nisa Fauziah; Hesti Lina Wiraswati; Ramdan Panigoro; Endang Yuni Setyowati; Afiat Berbudi (Journal of Tropical Medicine)
Malaria remains a public health problem and a leading cause of death worldwide. Consequently, the discovery of novel agents, including substances from medicinal plants, is urgently needed. Piper nigrum has long been used by the community in the treatment of the symptoms of malaria. In a previous study, Piper nigrum was demonstrated to exhibit promising antiplasmodial activity against Plasmodium falciparum 3D7 and INDO strains. The aim of this study was to further investigate the antimalarial activity (curative and prophylactic) of piperine (a major isolated constituent of Piper nigrum) in Plasmodium berghei ANKA-infected mice. Piperine 10, 20, and 40 mg/kg body weight (bw), artesunate 5 mg/kg bw, and DMSO were administered orally for four days to different groups of Swiss Webster mice. Then, mice were monitored for parasitaemia, body weight, rectal temperature, survival rate, and clinical parameters. Piperine 40 mg/kg bw in curative and prophylactic tests had the maximum parasitaemia chemosuppression of 79.21% and 58.8% (p < 0.05), respectively, with a significant effect on the survival rate compared with control animals. In the curative test, piperine 40 mg/kg bw reduced the mean clinical score compared with the control group. Additionally, piperine showed an ability to protect organs (lungs, liver, spleen, and kidneys) from some damage in a dose-dependent manner. This study can be used as a basis for further discovery of novel chemotherapeutic or chemoprophylactic compounds.